Exercise professional education, qualifications, and certifications: a content analysis of job postings in the United States - Pojednic, Rachele; O’Neill, Devin P.; Flanagan, Molly G.; Bartlett, Alexis; Carter, Byron LaGary; Kennedy, Mary A. (Frontiers in Sports and Active Living, 2024)
Introduction Growth in the field of clinical exercise science and the potential impacts on overall health and wellbeing have driven the need for qualified, clinically trained, exercise professionals. And yet, it is not well understood what specific credentials employers are seeking when hiring exercise professionals. Purpose The purpose of the study was to examine the qualification requirements for professionals seeking employment in exercise science, exercise physiology, kinesiology or equivalent fields. Methods Search platforms Indeed.com and USAJobs.gov were examined within a two week period in 2022. Search terms included “Exercise Physiology”, “Exercise Science”, “Exercise Professional”, “Exercise Prescription”, “Exercise Specialist”, and “Kinesiology”. Results A total of n = 739 jobs were retrieved and n = 615 jobs were included: Exercise Science (n = 227), Kinesiology (n = 210), Exercise Physiology (n = 91), Exercise specialist (n = 53), and Exercise prescription (n = 32). Over 70% of the jobs analyzed required a bachelor's degree with the remainder requiring various levels of education. The primary certification required was personal trainer (n = 94), followed by strength and conditioning specialist (n = 33), clinical exercise physiologist (n = 26), group exercise (n = 17), exercise specialist (n = 10), and exercise physiologist (n = 5). Four job focus areas were determined: academic teaching and research, general fitness and worksite wellness, athletic performance and rehabilitation, clinical exercise specialist all with varying levels of degree and certification requirements. Discussion Job postings related to exercise related professions are varied across the United States with wide-ranging education, credentialing and certification requirements. These findings indicate the timely need for outreach to employers to highlight changing credentialing requirements due to evolving accreditation standards.